The Notion of gharīb in Arabic Lexica - Baʿlabakkī, Ramzī Munīr (Journal of Abbasid Studies, 2019)
From very early in the Islamic linguistic tradition, the study of strange words, patterns, and constructions (gharīb) has been of interest. For the early philologists, words and expressions were “gharīb” when they were in use in the language of the Bedouins (Aʿrāb) but were rare in the contemporary language of those who collected the material. In this article, the early gharīb lexica and the development of the genre of gharīb works in later centuries is discussed, focusing on gharīb al-lugha (gharīb in the speech of the Arabs, kalām al-ʿArab), gharīb al-Qurʾān, and gharīb al-Ḥadīth, respectively.